Cardiac function and haemodynamics in alcoholic cirrhosis and effects of the transjugular intrahepatic portosystemic stent shunt. Issue 5 (1st May 1999) - Huonker, M; Schumacher, Y O; Ochs, A; Sorichter, S; Keul, J; Rössle, M
Abstract : BACKGROUND: A portosystemic stent shunt may impair cardiac function and haemodynamics. AIMS: To investigate the effects of a transjugular intrahepatic portosystemic shunt (TIPS) on cardiac function and pulmonary and systemic circulation in patients with alcoholic cirrhosis. PATIENTS/METHODS: 17 patients with alcoholic cirrhosis and recent variceal bleeding were evaluated by echocardiography and catheterisation of the splanchnic and pulmonary circulation before and after TIPS. The period of catheter measurement was extended to nine hours in nine of the patients. The portal vein was investigated by Doppler ultrasound before and nine hours after TIPS. RESULTS: Baseline echocardiography showed the left atrial diameter to be slightly increased and the left ventricular volume to be in the upper normal range. Nine hours after TIPS, the left atrial diameter and left ventricular end diastolic volume were increased (by 6% (p<0.01) and 7% (p<0.01) respectively); end systolic volume had not changed significantly. Invasive measurements showed a sharp increase in right atrial pressure (by 101%; p<0.01), mean pulmonary artery pressure (by 92%; p<0.01), pulmonary capillary wedge pressure (by 111%; p<0.01), and cardiac output (8.1 (1.6) to 11.9 (2.4) l/min; p<0.01). Systemic vascular resistance decreased (824 (242) to 600 (265) dyn·s·cm −5 p<0.01), and total pulmonary resistance increased (140 (58.5) to 188 (69.5) dyn·s·cm −5 ; p<0.05). Total pulmonary resistance (12%; NS), cardiac output (1.4 l/min; p<0.05), and portal vein blood flow (1.4 l/min; p<0.05) remained elevated for nine hours after TIPS in the subgroup. Portoatrial pressure gradient (43%; p<0.05), portohepatic vascular resistance (72%; p<0.05), and systemic vascular resistance (27%; p<0.01) were consistently reduced. CONCLUSIONS: The increase in the left atrial diameter, the pulmonary capillary wedge pressure, and total pulmonary resistance observed after the TIPS procedure reflected diastolic dysfunction of the hyperdynamic left ventricle in patients with alcoholic cirrhosis. The haemodynamic effects of the portosystemic stent shunt itself on the splanchnic circulation seem to be mainly responsible for the further decrease in systemic vascular resistance. TIPS may unmask a coexisting preclinical cardiomyopathy in patients with alcoholic cirrhosis and portal hypertension.